Entre os ratos, o sino e o gato: uma abordagem sobre o sistema penal e controle social na era da globalização a partir da análise do caso Bellingcat - Pinto, Fernanda Miler Lima (Universidade do Vale do Rio dos Sinos, 2021)
This research belongs to the contemporary agenda that discusses the relationship between Law and Technology. Considering the immersion in the Fourth Industrial Revolution, the focus of this investigation is the analysis of how a technology, exemplified by the case of investigation via OSINT (Open Source Intelligence) carried out by the online platform Bellingcat, may favor (or not) the growth of anti-formal laws trends in criminal knowledge and practice. Thus, the research problem that guided the steps of this study was: “How the wide use of technological innovations characteristic of the age of globalization, for the purposes of social control and criminal investigation, may provoke the growth of anti-formal legal tendencies in criminal knowledge and practice, having as a point of analysis the case of the investigation via OSINT carried out by the online platform Bellingcat?”. To achieve its goals, this work selected two cases in which the Bellingcat collective contributed with its investigations, the MH17 flight case and the Al-Werfalli case, to demonstrate how a research via OSINT works. Then, it was necessary to situate this reality in its context, for which knowledge on Globalization, Theory of Risk and Risk Criminal Law was accessed. Delving even further into the theme, the last part of this research was dedicated to dialoguing with some ideas of Orwell, Foucault and Deleuze about contemporaneity and, afterwards, it was developed about surveillance and its relationship with OSINT. This work comes from a monographic research, which uses the technique of indirect documentation data collection, based on different theoretical contributions that study the present time, from an inter-transdisciplinary perspective, linked to the notion of complexity. As for the results of this research, it is possible to ascertain that investigations via OSINT need standards, but they are not, by themselves, capable of increasing the insurgency of anti-formal legal formulas, so far. Despite this, the use of this method must be observed, as it is able to generate other effects, including in the legal world.
Keywords: OSINT; Bellingcat; Globalização; Direito; Sistema penal; Globalization; Law; Criminal system; ACCNPQ::Ciências Sociais Aplicadas::Direito